RAINBOW algorithm and its ability to resist RBS attacks and third party channels - Harmash, D.V. (Radiotekhnika, 2022)
The essence and possibilities of protecting the Rainbow post-quantum cryptographic algorithm are considered. The main properties of algorithms based on multidimensional quadratic transformations are studied. An assessment is given of what resources and computational energy are needed for the successful use of algorithms based on multidimensional quadratic transformations. The ability to protect the algorithm against attacks by third-party channels is analyzed. It is studied how successfully a cryptographic algorithm based on Rainbow multivariate quadratic transformations can withstand RBS attacks. A detailed description of the steps used to build an attack on a cryptographic algorithm based on Rainbow multivariate quadratic transforms is given. A structural analysis of the Rainbow algorithm is performed. Detailed conclusions are made regarding the performed analyzes. An assessment of the stability and complexity of the cryptographic encryption algorithm and electronic signature based on multivariate quadratic transformations is given.